Protective effect of left ventricular hypertrophy in right coronary artery occlusions - Gomes,Marne de Freitas (1999)
OBJECTIVE: To test the hypothesis that left ventricular hypertrophy (LVH) reduces the electrocardiographic and functional effects of right coronary artery occlusion. METHODS: We analysed 215 patients (166 males and 49 women,age of 58.9±10.6 years), with occlusion of the right coronary artery without other associated lesions. There was no significant difference (p>0.05) in age and gender distribution between the 78 patients with LVH (left ventricular mass >100g/m²) (Group A) when compared with the 137 patients without LVH (left ventricular mass <100g/m²) (Group B). RESULTS: The electrocardiographic finding of transmural necrosis was more often found in group B patients than in group A patients (56.9% and 30.8%, respectively; p<0.05). The left ventricular function parameters of group A were better than those of group B: the ratio end-diastolic pressure/systolic pressure (EDP/SP) (A: 0.108±0.036; B: 0.121±0.050; p<0.05); the end-diastolic volume index (A: 75.9±31.3ml/m²; B: 88.0±31.0ml/m²; p<0.01); the end-systolic volume index (A: 16.0±10.0ml/m²; B: 27.0 ±20.0ml/m²; p<0.001); the ejection fraction (A 78.6±10.8%; B 67.7±17.9%; p<0.001); the anteroinferior shortening (A: 43.9±10.3%; B: 35.1±12.8%; p<0.001). A higher degree of coronary tortuosity was observed in group A than in group B (78.2% and 24.1%; p<0.001) and also a more frequent absent or minimal diaphragmatic hypokinetic area (A: 80.8%; B: 54.0%; p<0.05). CONCLUSION: LVH reduces the effects of myocardial sequela and protects LV function when right coronary occlusion develops.